Efeito agudo de uma sessão de hipoterapia em parâmetros da marcha em idosos com e sem risco de quedas - Batista, Tatiele dos Santos (2023)
It is estimated that by 2025 the Brazilian population will be 11.3% over 65 years old. The aging process modifies viscoelastic, neural and muscular properties, interfering with balance, mobility and especially gait. Falls are multifactorial and result from loss of balance, neural and musculoskeletal inefficiency. There are various rehabilitation treatments that help the elderly to prevent falls, including hippotherapy, which uses the movement of the horse as a therapeutic resource. The aim of this study was to see if a session of hippotherapy can produce immediate effects on gait parameters in elderly people with and without a risk of falls. The research is characterized as a pre-experimental cross-sectional study and was carried out with 26 elderly people (10 males and 16 females) aged between 60 and 79 years (68.54 ± 5.68) registered with the family health strategy program in the municipality of Canguçu-RS. The selected subjects initially underwent a cognitive assessment using the MoCA, anthropometric assessment, level of physical activity using the IPAQ, gait assessment and Timed Up and Go (TUG) test with the aid of an inertial sensor. This was followed by a 30-minute hippotherapy session. To analyze gait and the Timed Up and Go test, a BTS GWALK® wearable inertial sensor and dedicated software were used to provide temporal and kinetic gait parameters (left and right gait quality, left and right support phase, left and right swing phase, gait duration, cadence, gait speed, processed steps, symmetry index, left and right propulsion, pelvic tilt, pelvic rotation, stride length) and parameters of the developmental phases during the execution of the TUG test (sitting to standing, standing to sitting, mid-turn, final turn). Thus, the study shows that a single session of hippotherapy produces acute effects on gait parameters and the TUG test.